Initial human T-cell leukemia virus type 1 infection of the salivary gland epithelial cells requires a biofilm-like structure - Nakamura, Hideki; Shimizu, Toshimasa; Takatani, Ayuko; Suematsu, Takashi; Nakamura, Tatsufumi; Kawakami, Atsushi (Virus research, 2019)
•The HTLV-1-infected cells have the extracellular matrix and linker proteins on their surface.•Biofilm-like components including agrin and tetherin were involved in transmission of HTLV-1 toward SGECs.•An electron microscopy confirmed transmission of virions at the interface between HCT-5 cells and SGECs. The initial phase of the human T cell leukemia virus-1 (HTLV-1) infection of salivary gland epithelial cells (SGECs) was examined. SGECs of patients with Sjögren’s syndrome (SS) and non-SS subjects were co-cultured with the HTLV-1-infected cell line HCT-5 or MOLT-4, then immunofluorescence (IF), scanning and transmission electron microscopy (SEM/TEM) were employed. The extracellular matrix and linker proteins galectin-3, agrin, and tetherin were expressed on the surfaces of both HCT-5 and MOLT-4 cells. HTLV-1 Gag-positive spots were observed on adjacent SGECs after 1 h of co-culture with HCT-5. Both in subjects with and those without SS, agrin and tetherin were co-expressed with HTLV-1 Gag on SGECs after co-culture with HCT-5, although no polarization of HTLV-1 Gag and relevant molecules was observed. SEM showed HTLV-1 virions that were found on HCT-5 were observed in the interfaces between HCT-5 cells and SGECs. TEM imaging showed that HTLV-1 virions were transmitted to SGECs at the interface with thin film-like structure, while HTLV-1 virions were released from the surface of HCT-5 cells. No endogenous retroviruses were observed. These results showed that the initial phase of HTLV-1 infection toward SGECs of SS was mediated not by viral synapses, but by biofilm-like components.